2021
DOI: 10.1186/s12904-021-00778-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between spiritual well-being and death anxiety in patients with gynecological cancer: a cross-section study

Abstract: Background In recent years, spiritual well-being has gradually gained the attention of health care providers in China, especially those in oncology departments, who have recognized the importance of improving spiritual well-being in cancer patients. Since most of the current research on spiritual well-being has been carried out in areas with religious beliefs, this study was conducted in the context of no development of formal religion. The purpose of this study was to explore the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 53 publications
2
31
0
2
Order By: Relevance
“…The primary aim of our main study was to explore the structure and validity of a Croatian version of the SWB32 with patient participants in Croatia. We found that this measure was comprehensible and acceptable to all participants, with quantitative findings broadly equivalent to those found in the international study with palliative patients [8], Median values of scale scores in our study were mostly consistent with those in other published studies [8,12,13,19]. For each of the four multi-item scales, the Cronbach's alpha coefficient was above the threshold of 0.6.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The primary aim of our main study was to explore the structure and validity of a Croatian version of the SWB32 with patient participants in Croatia. We found that this measure was comprehensible and acceptable to all participants, with quantitative findings broadly equivalent to those found in the international study with palliative patients [8], Median values of scale scores in our study were mostly consistent with those in other published studies [8,12,13,19]. For each of the four multi-item scales, the Cronbach's alpha coefficient was above the threshold of 0.6.…”
Section: Discussionsupporting
confidence: 89%
“…For sex, women scored higher on RSG, EX, RG, and Global-SWB. In the validation study [8,19], and the two Chinese studies [12,13], female participants also scored significantly higher on RSG, EX, and Global-SWB. Studies using other measures of spirituality or SWB (the Spiritual Interests Related to Illness Tool (SpIRIT) [33] and the Spiritual Needs Inventory (SNI) [35]) have also found that women have greater SWB than men [33][34][35][36].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Indeed, neuroticism (as a personality trait) is linked to generalized anxiety and preliminaries studies have demonstrated positive associations between neuroticism and death anxiety ( Loo, 1984 ; Frazier and Foss-Goodman, 1989 ; Pradhan et al, 2020 ). Elsewhere, it has also been demonstrated that people with high spiritual well-being have low death anxiety ( Routledge and Juhl, 2010 ; Lyke, 2013 ; MacLeod et al, 2019 ; Feng et al, 2021 ). Because spirituality offers sense of faith, meaning and purpose life and inner peace, people with high spirituality are less afraid of death and more prone to accept death.…”
Section: Introductionmentioning
confidence: 99%